Errors of Written English on the Outdoor Signs in Kupang City, Indonesia: Linguistic Landscape Approach - Nenotek, Seprianus A.; Beeh, Norci; Benu, Naniana N. (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
English is an international language familiar to everyone, relating to various social aspects. It can be found and easily seen or read in public spaces, such as on billboards or banners, and business names, such as shops, hotels, restaurants, transportation, and others. English is used in varied lingual forms and even the possibility of writing and grammatical errors. This research deals with the written English on outdoor signs in Kupang City, focusing on language errors and their causing factors. This research applied a qualitative analysis to explore the type of language errors found in written English in the outdoor signs, the outdoor signs that contain written English language errors, and the factors that cause language errors. The data for this study are the outdoor signs in Kupang City, East Nusa Tenggara, Indonesia that contain language errors in written English. All data are collected using photographic techniques using a digital camera. The next step is to transcribe the written English containing language errors and analyze the data qualitatively. The result of the study shows that the main errors are due to the spelling system, namely, deleting a sound and replacing the English sound with Indonesian. The analysis of the language errors also revealed that they are caused by English language competence and supported by the interference of the author or sign producers’ first language. This study may contribute significantly, especially for language learners, since English on outdoor signs can be used as authentic material for learning and English teaching and learning in schools.